2017
DOI: 10.1007/978-3-319-52234-0_23
|View full text |Cite
|
Sign up to set email alerts
|

Reachability for Dynamic Parametric Processes

Abstract: Abstract. In a dynamic parametric process every subprocess may spawn arbitrarily many, identical child processes, that may communicate either over global variables, or over local variables that are shared with their parent. We show that reachability for dynamic parametric processes is decidable under mild assumptions. These assumptions are e.g. met if individual processes are realized by pushdown systems, or even higherorder pushdown systems. We also provide algorithms for subclasses of pushdown dynamic parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The model considered in this paper can be extended with dynamic thread creation. Reachability is still decidable for this extension [32]. The decidability proof is based on upper closures and well-quasi orders, so it does not provide any interesting complexity upper bounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model considered in this paper can be extended with dynamic thread creation. Reachability is still decidable for this extension [32]. The decidability proof is based on upper closures and well-quasi orders, so it does not provide any interesting complexity upper bounds.…”
Section: Resultsmentioning
confidence: 99%
“…La Torre, Muscholl, and Walukiewicz [27] showed that the reachability problem remains decidable if instead of pushdown automata one considers higher-order pushdown automata, or any other automata model with some weak decidability properties. Reachability was also shown to be decidable for parametric pushdown systems with dynamic thread creation [32].…”
Section: Introductionmentioning
confidence: 99%
“…In a parallel development, several works have extended the basic model of parameterized systems (under the SC semantics) by considering processes that are infinite-state systems. The most dominant such class has been the case where the individual processes are variants of push-down automata [35,32,27,27,39,41,29] Parameterized verification is difficult, even under the original assumption of both SC and finite-state processes as we still need to handle an infinite state space. The extension to weakly consistent systems is even more complex due to the intricate extra process behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of more recent papers, parameterized verification has been considered in the case where the individual processes are push-down automata. [35,32,27,39,41,29].All the above works assume the SC semantics.…”
Section: Introductionmentioning
confidence: 99%